Assessment of starch branching and lamellar structure in rice flours. (July 2021) - Van Leeuwen, Matthew Paul; Toutounji, Michelle Rosemarie; Mata, Jitendra; Ward, Rachelle; Gilbert, Elliot Paul; Castignolles, Patrice; Gaborieau, Marianne
Highlights: Starch structure was characterised in rice flours by spectroscopy and scattering. The ability of starch structure to distinguish rices, growing conditions was explored. The link between average branching degree and apparent amylose content was assessed. Starch structure was affected by growing temperature, but not at all levels. The methods suitability for inclusion in rice quality analysis was assessed. Abstract: Apparent amylose content is used to describe milled rice flour composition. This spectrophotometric method is often the only direct measurement of starch structure in routine quality analysis. However, starch exhibits 6 levels of structure. The (supra)molecular starch structure in rice flours was measured: average degree of branching by 1 H NMR spectroscopy and semi-crystalline lamellar structure by small angle X-ray scattering (SAXS). The suitability of these methods in routine quality analysis for breeding programs or the food industry was assessed in terms of precision and accuracy. Determination of apparent amylose content exhibits high precision (ca 5 % error) but low accuracy. Determination of average degree of branching exhibits a similar precision but good accuracy. Sample preparation (dissolution) is the first source of error in 1 H NMR spectroscopy and presumably also in spectrophotometry. Within narrow ranges of apparent amylose content (less than 2.5 % absolute difference) differences in average degree of branching and lamellar structure could be observed. The difference between chemical structures of different amyloses/amylopectins within a given sample is not negligible. This opens a way to explore how finer details of molecular and supramolecular starch structure can play a role in understanding rice quality.